Quality of multigrain biscuits prepared by incorporation of concentrated whey - Shivabhai, Sutariya Harinkumar (Indian Journal of Dairy Science, 2017)
Whey is one of the major by-products of the dairy industry all over the world. The disposal of whey, because of its high BOD, requires appropriate treatment which adds to the cost of operation of dairy plants. In order to effectively use whey in the production of multigrain biscuits, the present investigation was initiated. The studies indicated that either paneer whey or cheese whey concentrated to 25 % TS can be used to replace up to 50 % water in the preparation of biscuits. This implied that whey concentrated to 12.5 % TS could replace water completely in the preparation of multigrain biscuits. The replacement resulted in improvement in sensory parameters, increased TS in biscuits and hence improved nutritive value. A baking temperature of 170 áµ’C / 25 min was observed to be optimal and incorporation of baking powder at 2000 ppm improved significantly the sensory parameters of whey incorporated multigrain biscuits.